Supernatural. Season eleven [videorecording (DVD)] - Kripke, Eric (Warner Bros. Entertainment Inc, 2016)
Season eleven plunges Sam and Dean Winchester (Jared Padalecki and Jensen Ackles) into extreme peril as they face The Darkness, a sinister new menace unleashed upon the Earth. They continue their monster-hunting missions, battling the usual werewolves, black-eyed demons and even a vengeful ghost in a stuffed bunny costume, but with a sharp new focus: destroy The Darkness. Needing all the help they can get, the brothers turn to fallen angel Castiel (Misha Collins); King of Hell Crowley (Mark A. Sheppard); and even an unassuming God (Rob Benedict) -- only to come face to face with Lucifer and Crowley's power-hungry witch mother, Rowena (Ruth Connell).